Construction of a novel brittleness index equation and analysis of anisotropic brittleness characteristics for unconventional shale formations - Ke-Ran Qian (KeAi Communications Co., Ltd., 2019)
Abstract The brittleness prediction of shale formations is of interest to researchers nowadays. Conventional methods of brittleness prediction are usually based on isotropic models while shale is anisotropic. In order to obtain a better prediction of shale brittleness, our study firstly proposed a novel brittleness index equation based on the Voigt–Reuss–Hill average, which combines two classical isotropic methods. The proposed method introduces upper and lower brittleness bounds, which take the uncertainty of brittleness prediction into consideration. In addition, this method can give us acceptable predictions by using limited input values. Secondly, an anisotropic rock physics model was constructed. Two parameters were introduced into our model, which can be used to simulate the lamination of clay minerals and the dip angle of formation. In addition, rock physics templates have been built to analyze the sensitivity of brittleness parameters. Finally, the effects of kerogen, pore structure, clay lamination and shale formation dip have been investigated in terms of anisotropy. The prediction shows that the vertical/horizontal Young’s modulus is always below one while the vertical/horizontal Poisson’s ratio (PR) can be either greater or less than 1. Our study finds different degrees of shale lamination may be the explanation for the random distribution of V ani (the ratio of vertical PR to horizontal PR).